Neonatal Gonocyte Differentiation in Mongolian Gerbil Meriones unguiculatus Involves Asynchronous Maturation of Seminiferous Cords and Rapid Formation of Transitional Cell Stage - Pinto, Maria Etelvina (2010)
This study describes the neonatal differentiation of the Mongolian gerbil gonocytes, focusing on the relationship between its relocation to the basement membrane, apoptosis and postrelocation changes and also the distribution of androgen receptors (AR). Testes of gerbils from I to 35 days of age (d) were examined by high resolution light microscopy and immunocytochemistry for proteins PCNA, VASA, and AR as well as by the TUNEL method. Gonocytes were quantified according to degree of relocation into nonrelocated, relocating and relocated. Most of them were found in the center of seminiferous cords at 1 d but a small number of relocating and relocated gonocytes were already visible in the first postnatal day. After relocation, gonocytes change phenotypically to a transitional stage designated herein prospermatogonia. Both gonocyte relocation and transformation into spermatogonial lineage occur asynchronously in the seminiferous cords, mainly after 7 d. Gonocyte proliferation began before but peak after their relocation to basement membrane at the prospermatogonia stage. Higher levels of gonocyte apoptosis were found at 7 d and 21 d. From this time onward gonocytes were not found. Gonocytes and prospermatogonia showed high amounts of AR in their cytoplasm contrary to spermatogonial subtypes, indicating a possible AR inactivation in these cells. In conclusion, the process of gonocyte relocation in the gerbil extends until the second postnatal week, leads to their rapid differentiation into prospermatogonia and occurs simultaneously with the loss of androgen sensitivity. Differently from other laboratory rodents, the events regarding gonocyte maturation in the gerbil last longer and occur asynchronously in seminiferous cords. Anat Rec, 293:310319, 2010. (C) 2009 Wiley-Liss, Inc.